FACTORS RELATED TO THE PRACTICE OF SELLING LIMITEDRESTRICTED OTC DRUGS IN SMALL SHOPS IN NORTH OBA DISTRICTIN 2025 - Sitti Hartinah; mardia habel; Sulviati Fidia Ningsih (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Based on data obtained from the Tidore Islands City Health Office, an inspection was conducted on kiosks/small stalls/stalls in several areas of North Oba District in 2023. The inspection results showed that of the 96 kiosks/small stalls in North Oba District, 74 (77%) were found to be selling restricted over-the-counter drugs despite not having a permit as a legal drug kiosk. The purpose of this study was to determine the factors related to the practice of selling restricted over-the-counter drugs in small stalls. This type of research used quantitative research with a descriptive design.cross sectional.There are four variables that have a relationship with the practice of selling restricted over-the-counter drugs: knowledge (p = 0.001), social environment (p = 0.003), economy (p = 0.000), supervision (p = 0.000). The knowledge of business actors and residents in the social environment greatly influences the practice of selling restricted over-the-counter drugs by business actors in small shops. Poor knowledge of both sellers and buyers about the dangers of restricted over-the-counter drugs sold without a doctor's prescription is still very high. In addition, low economic conditions and government supervision of the distribution of restricted over-the-counter drugs in small shops without official permits are among the factors that continue to be widespread in the practice of selling restricted over-the-counter drugs.